Conventional Ultrasound and Contrast-Enhanced Ultrasound in Hepatic Epithelioid Hemangioendothelioma: Retrospective Evaluation in 20 Cases - Qiu, Tingting; Zhu, Dongmei; Fu, Rong; Luo, Yan; Ling, Wenwu (Frontiers in Oncology, 2022)
Objectives This study aimed to analyze the patterns of conventional ultrasound (CUS) and contrast-enhanced ultrasound (CEUS) in 20 patients with diagnosis of hepatic epithelioid hemangioendothelioma (HEHE). Methods Twenty patients (12 females and 8 males) with mean age of 43.6±13.6 years were included in this study from January 2012 to May 2020. CUS and CEUS features of the twenty patients with histologically proven HEHE were retrospectivity reviewed by two radiologists. The clinical manifestations and the pathological findings of all patients with HEHE are described. Results There were 3 types of HEHE on CUS, including single nodular (8/20, 40%), multifocal nodular (10/20, 50%), and diffuse type (2/20, 10%). The mean size of lesions was 4.2±2.6 cm. B-mode ultrasound of HEHE showed hypoechoic (15/20, 75%), heterogeneous echogenicity (4/20, 20%), or hyperechoic (1/20, 5%) lesions with regular shape (18/20, 90%) near the liver capsule (17/20, 85%), and occasionally with a halo (4/20, 20%) and calcifications (3/20, 15%). Eight out of the 20 patients also had CEUS. On CEUS, HEHE demonstrated peripheral rim-like (5/8, 62.5%), heterogeneous (2/8, 25%), or homogeneous (1/8, 12.5%) hyperenhancement in the arterial phase. All patients (8/8, 100%) showed hypoenhancement in the portal and late phase. CEUS detected more lesions than CUS in 3 patients (3/8, 37.5%). In addition, central irregular unenhanced zones were observed in 6 patients (6/8, 75%). Conclusions CUS and CEUS demonstrated specific findings for HEHE, which includes multifocal hypoechoic lesions in a subcapsular distribution with typical enhancement characteristics of malignant hepatic tumors.